ANALISIS ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SETELAH PENGUMUMAN DIVIDEN PT.KALBE FARMA SAAT PANDEMI COVID-19 - Amin, Mohammad Arridho Nur (Creative Research Management Journal, 2022)
PT. Kalbe Farma became one of the issuers that during the Covid-19 pandemic earned alarge profit per share, so this study aims to see if there is abnormal return and tradingvolume activity around the date of dividend announcement made by PT. Kalbe Farma duringthe Covid-19 pandemic. The event study method is used to study the reaction of theIndonesian Capital Market during the observation period. The observation period is carriedout five days before the dividend announcement and five days after the dividendannouncement of PT. Kalbe Farma. Secondary data used in this study are data on the closingprice of daily shares, daily JCI, daily trading volume, and the number of outstanding shares.The results found that there were abnormal differences in returns before and after dividendannouncements, and there were also differences in trading volume of activity before and afterthe dividend announcement of PT. Kalbe Farma.